Myth, ritual, and society in Mycenaean Anatolia: identifying Asian influences - Woodard, Roger D. (Cambridge University Press, 2025)
Despite the Mycenaean Linear B script having been deciphered some seventy years ago, much has remained uncertain regarding the ritual ideology of Mycenaean society that the Linear B documents reveal. Roger Woodard here explores this problem by investigating a new range of sources from the Late Bronze Age and Early Iron Age, together with processes of the transfer of knowledge between Anatolia and European Hellas. Bringing together evidence from Mycenaean culture with mythic and cult traditions of Iron Age Greek culture and Indo-Iranian sources, he reveals the close parallels between Mycenaean and Vedic ritual structures and practices, these being particular expressions of Mycenaean Asianism. He also demonstrates how features inspired from Indo-Iranian sources are present in Aeolian Greek epic traditions that emerged during the Iron Age, notably the Argonautic search for the Golden fleece.